Shotgun Proteomic Analysis of Thermally Challenged Reef Corals - Mayfield, Anderson B.; Aguilar, Catalina; Kolodziej, Graham; Enochs, Ian C.; Manzello, Derek P. (Frontiers in Marine Science, 2021)
Although coral reef ecosystems across the globe are in decline due to climate change and other anthropogenic stressors, certain inshore reefs of the Upper Florida Keys reef tract have persisted, with some even thriving, under marginalized conditions. To better understand the molecular basis of the thermotolerance displayed by these corals, a laboratory-based temperature challenge experiment that also featured conspecifics from a more stress-susceptible offshore reef was conducted with the common Caribbean reef-builder Orbicella faveolata, and the proteomes of both the coral hosts and their endosymbiotic dinoflagellate communities were profiled in (1) controls, (2) corals that succumbed to high-temperature stress and bleached, and (3) those that instead acclimated to high temperatures ex situ. Proteomic signatures varied most significantly across temperatures, host genotypes, and Symbiodiniaceae assemblages, and the two eukaryotic compartments of this mutualism exhibited distinct proteomic responses to high temperatures. Both partners maintained high levels of molecular chaperones and other canonical (eukaryotic) stress response (CSR) proteins in all treatments (including controls). Instead, proteins involved in lipid trafficking, metabolism, and photosynthesis played greater roles in the holobionts’ high-temperature responses, and these energy mobilization processes may have sustained the elevated protein turnover rates associated with the constitutively active CSR.